Evaluation of introduced varieties of maize (Zea mays L.) in Sarawak - Zainal Abidin, Mohamad Idris (Penerbit Universiti Kebangsaan Malaysia, 1980)
Seven flint and dent type maize varieties from the International Maize and Wheat Improvement Center (CIMMYT), Mexico, one sweet corn variety from Hawaii and two sweet corn varieties from Peninsular Malaysia were evaluated for their grain yield and shelling percentages in Sarawak during the padi off-season. Among the flint and dent types, five varieties, CIMMYT 2.3,4.5 and 8 yeild over 4.0 ton/ha and merit attention. Their shelling percentages were satisfactory. Among the sweet corn varieties, variety Chinta was most promising for seed production while the lowest yielding variety. Hawaiian Supersweet 9 showed poor performance. Further evaluation of these varieties in the following padi main season is recommended before any conclusion can be made.